Active Ground-floors - Gkioka, Dimitra; Xanthopoulou, Maria (Sens public, 2024)
The project is located in Thessaloniki, in a very distinct neighborhood, in the western part of the city center. Characteristic of this place is the social, economic and urban degradation and the large number of vacant and non-operative ground floor spaces. As we began our field study, we also noticed a large number of informal local communities, from a variety of cultural and ethnic backgrounds, who were willing to interact with us and engage with their neighborhood. ¶ The typology of buildings in this area is the classic Greek “polykatoikia” from the 60’s and 70’s that combine housing in the upper floors and commercial stores in the ground floor. However, in the last decade, the effects of the economic crisis have left that part of the ground floors empty, locked and not representing any aspect of urban life. The main idea of the project is to convert these places into urban commons in order to involve local citizens in this idea and make use of them. A variety of proposals for alternative uses encourage exchange, collaboration and participation that will build new relationships, networks, empowerment, inclusion and solidarity. ¶ To implement this change, a series of steps were planned to establish a partnership between the private owners of the ground floors and the financier of the project (city municipality or other public institution ). The design proposals and the proposed interventions are all temporary in order to return the space to its original state at the end of the program.